Carbon, Metals, and Grain Size Correlate with Bacterial Community Structure in Sediments of a High Arsenic Aquifer - Legg, Teresa; Zheng, Yan; Simone, Bailey; Radloff, Kathleen A.; Mladenov, Natalie; González Peña, Antonio; Knights, Dan; Siu, Hosea; Rahman, M. M.; Ahmed, K. M.; McKnight, Diane M.; Nemergut, Diana R. (Frontiers in Microbiology, 2012)
Bacterial communities can exert significant influence on the biogeochemical cycling of arsenic (As). This has globally important implications since As toxicity in drinking water affects the health of millions of people worldwide, including in the Ganges-Brahmaputra Delta region of Bangladesh where geogenic groundwater arsenic concentrations can be more than 10 times the World Health Organization’s limit. Thus, the goal of this research was to investigate patterns in bacterial community composition across environmental gradients in an aquifer with elevated groundwater As concentrations in Araihazar, Bangladesh. We characterized the bacterial community by pyrosequencing 16S rRNA genes from aquifer sediment samples collected at three locations along a groundwater flowpath, at a range of depths between 1.5 and 15 m. We identified significant shifts in bacterial community composition along the groundwater flowpath in the aquifer. In addition, we found that bacterial community structure was significantly related to sediment grain size, and sediment carbon (C), manganese (Mn), and iron (Fe) concentrations. Deltaproteobacteria and Chloroflexi were more abundant in silty sediments with higher concentrations of C, Fe, and Mn. By contrast, Alphaproteobacteria and Betaproteobacteria were more abundant in sediments with higher concentrations of sand and Si, and lower concentrations of C and metals. Based on the phylogenetic affiliations of these taxa, these results may indicate a shift to more Fe-, Mn-, and humic substance- reducers in the high C and metal sediments. It is well-documented that C, Mn and Fe may influence the mobility of groundwater arsenic, and it is intriguing that these constituents may also structure the bacterial community.